Measuring the size and impact of public cash support for children in cross-national perspective - Francesco Figari; Alari Paulus; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2009)
The paper focuses on the support given through tax and benefit systems to families with children and addresses how the size and impact on the income distribution of this kind of support can be accurately measured. While such support is usually measured in rather narrow terms by adding up the benefits explicitly labelled as being for children, we adopt a more comprehensive approach whereby all tax-benefit instruments (or their components) which are contingent on the presence of children are accounted for. We use EUROMOD, the European Union tax-benefit microsimulation model, to quantify the support for children and analyse its impact on household incomes and child poverty for 19 countries. We find that the conventional approach underestimates on average the total amount of support for children by about one fifth. Furthermore, accounting for the net effect of the full range of components of cash support makes little difference fifth. Furthermore, accounting for the net effect of the full range of components of cash support makes little difference in some countries but a lot more in others. For cross-national comparisons it is therefore critical that a comprehensive measure is adopted.
Keywords: C81; D31; H23; 330; children; taxes and cash benefits; child poverty; European Union; microsimulation; Sozialpolitik; Familienleistungsausgleich; Steuerbegünstigung; Öffentlicher Transfer; Kinderarmut; EU-Staaten